CITRA INSTITUSI, KEPERCAYAAN MAHASISWA, DAN NILAI JASA PENDIDIKAN TINGGI SEBAGAI VARIABEL ANTESEDEN DARI LOYALITAS MAHASISWA - Marcellia Susan (Media Riset Bisnis & Manajemen, 2011)
As an institution which holds an important role in the process of human resource development, a higher education also has responsibility in giving good quality. Even though the need of education makes the demand of education services, the existence of many same services by competitor makes every higher education has to offer the best quality of education services and also has to do many efforts for survival. As an organization which offers service with unique characteristics, the demand of service of a higher education often depends on people trust and the image of the institution. These two factors could influence student perception of the service and at last could influence their loyalty to the institution. In this research, the students as user of the service which has been offered by higher education, become analysis unit. Descriptive analysis has been done to get the descriptive of the institution image, student trust, education service value, and student loyalty to the institution. Verificative analysis has also been done to test the relationship between these variables. The result of this research shows that the students have positive perception about the institution image, and they have faith that the institution would take the most right action which could help students in achieving carrier and learning objectives. The students also analyze the relationships between what they receive and what they give, and it could influence their loyalty. And based on the results of estimation coefficients of the influences among variables, it could be concluded the existence of the interrelationships among research variables. In this case, institution image and student trust affect the service value, and institution image, student trust, and service value of study programs affect student loyalty.Keywords: Higher education service, Institution image, Student trust, Service value, Student loyalty